Diabetic ketoacidosis in pregnancy – Case series, pathophysiology, and review of the literature. (February 2022) - Eshkoli, Tamar; Barski, Leonid; Faingelernt, Yaniv; Jotkowitz, Alan; Finkel-Oron, Alona; Schwarzfuchs, Dan
Abstract: Objective: Diabetic ketoacidosis (DKA) during pregnancy is a life-threatening emergency for both the mother and the fetus. The pathophysiology of DKA in pregnancy has its own characteristics due to multiple factors, such as insulin resistance, accelerated starvation and respiratory alkalosis, thus creating ketosis-prone state, with DKA occurring at milder degrees of hyperglycemia, even in normoglycemic levels, which can result in delayed diagnosis and treatment with potential for adverse metabolic consequences. Study design: In this article, we presented 8 clinical cases of DKA during pregnancy. We discuss the spectrum of the clinical picture, the entity of euglycemic DKA vs hyperglycemic DKA, the period of pregnancy in appearance of episode of DKA and triggers of DKA. Conclusion: The treatment of DKA in pregnant women must be started immediately and must be accentuated on intravenous fluids, insulin and electrolyte replacement. DKA in pregnancy may be euglycemic. Prevention, early recognition, immediate hospitalization, and aggressive management remain the cornerstones in DKA management in pregnancy.